Pengaruh Teknik 6 Seconds Slow Deep Breathing Terhadap Tekanan Darah Pada Penderita Hipertensi - Apriani, Putri; Obar, Obar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Hypertension is one of the most common diseases worldwide and can lead to various complications. 6 seconds of slow deep breathing is a relaxation technique that can help reduce stress and blood pressure. This study aims to determine the effect of the 6-second slow deep breathing technique on lowering blood pressure in patients with hypertension. The research method used was quantitative with a quasi-experimental pre-test and post-test design on 24 eligible respondents in the Puskesmas Cianjur Kota. The 6-second slow deep breathing technique was found to have an effect on lowering blood pressure in patients with hypertension. Statistical results using the Wilcoxon test showed a p-value of 0.000 (<0.05). There is an effect of the 6-second slow deep breathing technique on blood pressure levels in hypertension patients at the Puskesmas Cianjur Kota in 2025. It is hoped that community health center staff can develop 6-second slow deep breathing therapy as an alternative therapy for managing blood pressure in hypertension patients